Social media in Trinidad : values and visibility - Sinanan, Jolynna (Why we post., 2017)
Drawing on 15 months of ethnographic research in one of the most under-developed regions in the Caribbean island of Trinidad, this book describes the uses and consequences of social media for its residents. Jolynna Sinanan argues that this semi-urban town is a place in-between: somewhere city dwellers look down on and villagers look up to. The complex identity of the town is expressed through uses of social media, with significant results for understanding social media more generally. Not elevating oneself above others is one of the core values of the town, and social media becomes a tool for social visibility; that is, the process of how social norms come to be and how they are negotiated. Carnival logic and high-impact visuality is pervasive in uses of social media, even if Carnival is not embraced by all Trinidadians in the town and results in presenting oneself and association with different groups in varying ways. The study also has surprising results in how residents are explicitly non-activist and align themselves with everyday values of maintaining good relationships in a small town, rather than espousing more worldly or cosmopolitan values.